Kontradiksi sharia compliance dalam Islam pada asuransi - Istianah, Nur (Maliki Interdisciplinary Journal, 2024)
This study aims to determine the contradictions in the understanding and implementation of sharia compliance in the context of insurance in Islam. By analyzing different scholars’ views and approaches to insurance, this study highlights the differences in interpretation and application of Islamic law regarding Insurance practices. Factors such as insurance history, operations, and socio-economic implications are also explored in achieving shariah compliance of insurance practices. This research provides insights on how to overcome such contradictions in order to achieve better harmony between insurance and Shariah values.